2019
DOI: 10.1038/s41366-019-0460-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an acute bout of exercise on circulating extracellular vesicles: tissue-, sex-, and BMI-related differences

Abstract: Background. Exercise is recognized to evoke multisystemic adaptations that, particularly in obese subjects, reduce body weight, improve gluco-metabolic control, counteract sarcopenia and lower the risk of cardiometabolic diseases. Understanding the molecular and cellular mechanisms of exercise-induced benefits is of great interest due to the therapeutic implications against obesity.Objectives and methods. The aim of the present study was to evaluate time-related changes in size distribution and cell origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 40 publications
2
63
1
1
Order By: Relevance
“…Some studies in humans and rodents observed an immediate increase of sEVs after a single bout of physical exercise (Frühbeis et al, 2015;Bei et al, 2017;Oliveira et al, 2018;Whitham et al, 2018;Brahmer et al, 2019). One study found a direct reduction of total EV numbers, while detecting an increased population of muscle cell-derived EVs (Rigamonti et al, 2019). Furthermore, elevation of resting EV levels were detected in response to long-term exercise interventions (Chaturvedi et al, 2015;Bei et al, 2017;Bertoldi et al, 2018;Ma et al, 2018), though Hou et al (2019) could not detect changes in EV levels.…”
Section: Evs In Physical Exercisementioning
confidence: 99%
See 3 more Smart Citations
“…Some studies in humans and rodents observed an immediate increase of sEVs after a single bout of physical exercise (Frühbeis et al, 2015;Bei et al, 2017;Oliveira et al, 2018;Whitham et al, 2018;Brahmer et al, 2019). One study found a direct reduction of total EV numbers, while detecting an increased population of muscle cell-derived EVs (Rigamonti et al, 2019). Furthermore, elevation of resting EV levels were detected in response to long-term exercise interventions (Chaturvedi et al, 2015;Bei et al, 2017;Bertoldi et al, 2018;Ma et al, 2018), though Hou et al (2019) could not detect changes in EV levels.…”
Section: Evs In Physical Exercisementioning
confidence: 99%
“…Furthermore, elevation of resting EV levels were detected in response to long-term exercise interventions (Chaturvedi et al, 2015;Bei et al, 2017;Bertoldi et al, 2018;Ma et al, 2018), though Hou et al (2019) could not detect changes in EV levels. ExerVs appear as a complex mixture of vesicles originating from platelets (Frühbeis et al, 2015;Brahmer et al, 2019), endothelial progenitor, or endothelial cells (Ma et al, 2018;Brahmer et al, 2019;Hou et al, 2019), leukocytes (Brahmer et al, 2019), and muscle cells (Guescini et al, 2015;Whitham et al, 2018;Rigamonti et al, 2019), which most probably varies depending on exercise mode and time of investigation.…”
Section: Evs In Physical Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that acute AE was associated with an increase in EV concentration and the presence of twelve different miRNA in their cargo (46). In contrast, in obese adults, Rigamonti et al (2019) reported reduced EVs concentration immediately at the end of AE and after 3h and 24 h (47). No studies have been conducted on EV release with AE in youth with obesity to our knowledge.…”
Section: Discussionmentioning
confidence: 99%